Experience capitalization: Public, private, producer partnerships in East Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
This report comprises 12 case stories produced through the Experience Capitalization project implemented by CTA in different parts of the world. These cases report on experiences in Kenya, Rwanda and Tanzania with Public, Private, Producer Partnerships (4Ps) to deliver agricultural value chain projects.